2020
DOI: 10.46490/bf435
|View full text |Cite
|
Sign up to set email alerts
|

Surface sterilization of English oak (Quercus robur L.) acorns using wet water steam

Abstract: Effective and environmentally friendly methods of protection to reduce seed contamination from fungi are constantly sought. The use of thermal impulses of 100 °C wet water steam to reduce fungal contamination has not been sufficiently investigated, and the potential of this physical approach has not been estimated.The aim of the study was to investigate what impact 100 °C wet water steam with different time durations had on acorn contamination with fungi, acorn germination and biometric indicators of English o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…Since the commonly performed thermotherapy treatment (at 41 • C for 2.5 h) can lead to the proliferation of ubiquitous fungal species during acorn storage [39,41,44,45], the second part of this study focused on the impact of different thermotherapy and short-term storage conditions on the internal acorn mycobiota. Generally, among the ten most frequently isolated species were Penicillim glandicola, P. glabrum, Fusarium solani, F. avenaceum, and Alternaria alternata, which was not surprising as members of these genera were reported to be the most common potentially harmful fungi inhabiting Quercus robur acorns in similar studies [11,27,32,33,66]. Several other frequently isolated species in this research were reported as plant pathogens by other authors, although not on oak acorns.…”
Section: Discussionsupporting
confidence: 74%
“…Since the commonly performed thermotherapy treatment (at 41 • C for 2.5 h) can lead to the proliferation of ubiquitous fungal species during acorn storage [39,41,44,45], the second part of this study focused on the impact of different thermotherapy and short-term storage conditions on the internal acorn mycobiota. Generally, among the ten most frequently isolated species were Penicillim glandicola, P. glabrum, Fusarium solani, F. avenaceum, and Alternaria alternata, which was not surprising as members of these genera were reported to be the most common potentially harmful fungi inhabiting Quercus robur acorns in similar studies [11,27,32,33,66]. Several other frequently isolated species in this research were reported as plant pathogens by other authors, although not on oak acorns.…”
Section: Discussionsupporting
confidence: 74%
“…Other studies on Quercus spp. confirmed the association of the exposure of acorns to thermotherapy with higher acorn viability, germination rates, and the earlier and more uniform germination [29,30,32,36]. The latter was also noticed in this research (personal observation, data not shown).…”
Section: Discussionsupporting
confidence: 88%
“…Fungal infections can also be successfully prevented or controlled by storing the acorns under the adequate conditions and by applying eradicative treatments which target harmful pathogens prior to storage. Detrimental fungi can be inhibited or eliminated from the acorns with the use of fungicides, biological control agents (antagonistic fungi or bacteria), disinfectants, steam or hot water [28][29][30]. The use of the latter two is referred to as a thermotherapy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations